Pengembangan Media Pembelajaran Berbaasis Komputer tentang Pembelajaran Kontekstual untuk Pelatihan Guru Sejarah SMA di LPMP Provinsi Maluku Ambon - La Ode Safihu (Paedagogik, 2013)
This research was aimed at developing computer-based teaching media about the contextual teaching for the training of senior high school teachers of History, so that they could understand and professionally implement contextual teaching toward their students. The sample of this research consisted of 43 senior high school teachers, consisting of three teachers to be individually tried out, 10 teachers to be tried out in small groups, and 30 teachers to be tried out in the field. The data in this research were obtained from two sources. The teaching materials and instructional aspects were obtained from subject-matter experts. The media lay out and programming was obtained from experts in media making. For the field try out, the obtained data were teaching materials, instructional aspect, lay out aspect, and programming aspect. The instruments for collecting the data were questionnaires filled in by the subject-matter experts, the experts in media making, and questionnaires to be tested in the field were filled in by teachers. The data were then analyzed qualitatively and quantitatively. The result of the try out shows that the quality of the contextual teaching media which were developed for the training of senior high school teachers of History was rated very good. It can be seen from the teaching material aspect with an average score of 4.53, instructional aspect with an average score of 4.54, the lay out aspect with an average score of 4.57, and the programming aspect with an average score of 4.59. Based on the result of the try out, it can be concluded that the developed teaching media can be used in the training of senior high school teachers of History, because it has fulfilled the required criteria that is the result of the field try out should be at least good. Therefore, the developed media can be considered valid and can be used for the training of the senior high school teachers of History in LPMP Maluku, Ambon.